1979
DOI: 10.1002/nur.4770020405
|View full text |Cite
|
Sign up to set email alerts
|

The use of modeling to teach empathy to nursing students

Abstract: Various combinations of modeling, labeling, and rehearsal (videotaped) were used to teach empathy to four experimental groups; a fifth group served as a no‐treatment control. The subjects were 56 junior and senior baccalaureate nursing students, all of whom were women. A repeated‐measures design was employed, with posttesting immediately following treatment and 3 weeks later. Learning was measured by means of a written test (Empathy Test) and an interview that was evaluated using the Barrett‐Lennard Relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

1981
1981
2007
2007

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 36 publications
1
49
0
1
Order By: Relevance
“…A few methods of measuring empathy have also been developed for use in nursing. These include the Empathy Construct Rating Scale (17), the Empathic Understanding of Interpersonal Processes Scale (18), the empathy subtest of the Relation Inventory (19), and the Empathy Test (20). None of these scales was specifically developed to measure physician empathy and, therefore, may not capture the essence of empathetic care rendered by physicians.…”
Section: Physician Empathymentioning
confidence: 99%
“…A few methods of measuring empathy have also been developed for use in nursing. These include the Empathy Construct Rating Scale (17), the Empathic Understanding of Interpersonal Processes Scale (18), the empathy subtest of the Relation Inventory (19), and the Empathy Test (20). None of these scales was specifically developed to measure physician empathy and, therefore, may not capture the essence of empathetic care rendered by physicians.…”
Section: Physician Empathymentioning
confidence: 99%
“…The third phase of the process involves the nurse's detachment, her ejection of the other's ego and her examination of the internalised con tent. Layton (1979) describes a psychological pro cess of empathy made up of three compo nents; the empathic state of the nurse, the communication of empathy from nurse to client, and the perception of a nurse's empa thic state by the client. Empathy therefore in volves a personality predisposition (sensitivity), an experienced emotion (sensing and feeling the client's predicament) and a cognitive and behavioural aspect (under standing the client and communicating this un derstanding in a language attuned to a client's current feelings, and the client's perception of this feeling).…”
Section: The Empathic Processmentioning
confidence: 99%
“…In essence, a 3.0 response conveys under standing of how the client feels (affect) and the meaning (content) attached to those feel ings. On all these scales empathy is rated by judges (independent observers) and several in vestigators have found that inter-judge relia bility is a problem with these measurements (Layton 1979;Janzen 1984).…”
Section: The Measurement Of Empathymentioning
confidence: 99%
“…The position of nurse educators attributes and modelling on student caring behaviours has also been the subject of investigation. (Layton 1979;Watson 1979) Bush (1988:169) posits that student nurses must grow in insight about themselves as caring persons before they can understand the person who needs care.…”
Section: The Research Designmentioning
confidence: 99%